Impressed current cathodic protection (ICCP) of mild steel in association with zinc based paint coating - Deshpande, Pravin; Kolekar, Aniket; Bhopale, Abhijit; Kalendová, Andréa; Kohl, Miroslav (My University, 2022)
In this study, an epoxy ester resin-based paint formulation incorporating spherical zinc as a pigment with a size range of 1–2 µm is investigated for usage in conjunction with impressed current cathodic protection, and the results are presented. Painted mild steel containing spherical zinc PVC = 61% exhibits negligible iron loss ∼ 0.48 ppm when used under impressed current condition.Electrochemical corrosion of mild steel is significantly reduced.This can be attributed to the combined effect of sacrificial protection by zinc pigments and supply of electrons by the impressed current system. Lower protection potential will be required when mild steel is painted by a coating containing spherical zinc PVC = 61% under impressed current application.
Katodická ochrana vloženým proudem (ICCP) měkké oceli ve spojení s nátěrem na bázi zinku
Keywords: cathodic protection; impressed current technique; cathodic polarization; corrosion protection; katodická ochrana; technika vloženého proudu; katodická polarizace; ochrana proti korozi